2021
DOI: 10.25304/rlt.v29.2482
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness of immersive VR simulations in undergraduate science learning: lessons from a media-comparison study

Abstract: Our main goal was to investigate if and how using multiple immersive virtual reality (iVR) simulations and their video playback, in a science course, affects student learning over time. We conducted a longitudinal study, in ecological settings, at an undergraduate field-course on three topics in environmental biology. Twenty-eight undergraduates were randomly assigned to either an iVR-interaction group or a video-viewing group. During the field-course, the iVR group interacted with a head-mounted device-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 55 publications
1
12
0
1
Order By: Relevance
“…Taken together and viewed through the lens of Biggs’s (1993) model of Presage, Process, and Product (described in Section “Theoretical framework”), the results suggest that for learners with longitudinal exposure to VR simulations, there is an advantage of iVR over dVR with respect to fostering emotional engagement but not at the cost of learning effectiveness. iVR is often considered an overwhelming experience for students (Makransky et al, 2017; Pande et al, 2021; Parong & Mayer, 2018); our study corroborates this concern and further suggests that iVR learners may benefit specifically from longitudinal exposure to immersive virtual environments.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Taken together and viewed through the lens of Biggs’s (1993) model of Presage, Process, and Product (described in Section “Theoretical framework”), the results suggest that for learners with longitudinal exposure to VR simulations, there is an advantage of iVR over dVR with respect to fostering emotional engagement but not at the cost of learning effectiveness. iVR is often considered an overwhelming experience for students (Makransky et al, 2017; Pande et al, 2021; Parong & Mayer, 2018); our study corroborates this concern and further suggests that iVR learners may benefit specifically from longitudinal exposure to immersive virtual environments.…”
Section: Discussionsupporting
confidence: 82%
“…Considering the potential impact of novelty for desktop-based virtual experiences, we predict that for dVR students in our study, their affective responses and objective learning outcomes would decrease from the first to the second VFT. With respect to the novelty effect in iVR learning simulations, a prediction is much more difficult because only two longitudinal studies have been published (Huang et al, 2020; Pande et al, 2021). Pande et al (2021) described (without statistical analysis) that students’ perceived learning and enjoyment tend to persist over multiple iVR sessions in a study about learning in environmental biology.…”
Section: Literature Review and Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of new, innovative digital supplemental resources represents a continuing challenge for physiology educators and researchers. From the use of quick response codes ( 44 ) to the use of virtual reality ( 45 ), it is difficult to know which newer forms of digital supplementation might play a role in student success. This study represents a significant contribution to physiology education by providing a survey that will help instructors decide whether/which digital supplemental resource(s) to recommend to students, a critical but underserved part of student learning.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey, the students reported that the short VR simulations enhanced their understanding of topography and engagement with the topic. Likewise, Pande et al [16] conducted a quasi-experiment in a biology course in which bachelor students viewed a total of three simulations either as video or with a VR headset. The comparative study showed a greater increase in knowledge gain and improved knowledge retention in the VR condition.…”
Section: Stream 2: Short-term Vr Experimentsmentioning
confidence: 99%